Penerapan Augmented Reality Markerless pada E-Commerce Tanaman Hias Berbasis Web dan Mobile - Andika Kukuh Prasetyo; Wahyu Sri Utami (SOTVI - Society of Visual Informatics, 2026)
This study presents the development of an ornamental plant e-commerce system integrated with Markerless Augmented Reality (AR) technology, supporting both web and mobile platforms. The system addresses two identified problems: SME ornamental plant sales that still rely on informal social media without structured management, and the inability of online buyers to visualize products in their real environment before purchasing. The system was developed using the Waterfall method. The mobile application uses Flutter, the web admin dashboard uses Laravel with Filament, and the AR module uses Unity with ARFoundation and Google ARCore, all connected through a RESTful API with MySQL as the primary database, and integrated with Midtrans for payment and RajaOngkir for shipping. System verification was conducted through Black Box Testing and AR Performance Testing. Black Box Testing confirmed that all 15 mobile and 11 web admin test scenarios produced expected outputs, achieving a 100% success rate. AR Performance Testing on two Android devices showed stable performance on the Infinix GT 30 Pro (Dimensity 8350 Ultimate), while the Xiaomi Redmi Note 13 5G (Dimensity 6080) experienced frame rate fluctuations due to thermal throttling; neither device encountered force close or crash. These results confirm the system functionally addresses both problems: providing a structured digital sales platform for ornamental plant SMEs and enabling buyers to visualize plants in their real environment before purchasing.